Understanding and Predicting Localised Variations in the Degradation Rate of Architectural, Organically Coated, Steel Cladding - Tim Savill; Eifion Jewell (Buildings, 2023)
Organically coated architectural steel provides an economic, visually attractive, innovation friendly and robust building cladding. However, its performance, usually calculated using accelerated weathering and ‘artificial’ outdoor weathering testing, can be compromised within specific areas of the building envelope. The exact reasons for this are not fully understood. In an attempt to discern where and why performance varies, an investigation is carried out into some possible reasons for the performance discrepancy, and it is concluded that a combination of high humidity and the build-up of aggressive natural deposits contribute to high degradation rates in sheltered regions, such as building eaves, where microclimates are created. The build-up of deposits and their effect is presented as a key degradation accelerant during in-use service. A numerical simulation approach is developed to predict the natural washing, via rain impact and characteristics of the building analysed. This approach shows promise for determining areas unlikely to be naturally washed, and therefore subjected to a degradation accelerating, build-up of deposits. It is shown that such a simulation could be used to optimize the building design process to promote natural washing as well as provide an area-of-concern map in which exposed cut edge should be avoided and any manual inspection should be concentrated. It is also shown that nearby buildings can provide sheltering effects leading to decreased natural washing, increased deposit build-up and ultimately accelerated failure.